How Accounting Information System Reflects on Resignation Intentions & Job Satisfaction: Gen-Z Effect - Valdiansyah, Riyan Harbi; Karjono, Karjono; Novitasari, Desi; Nurhadinah, Nurhadinah (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
This study investigates the influence of Accounting Information Systems on employee resignation intention, with job satisfaction operating as a mediating factor. Employee satisfaction may reduce the likelihood of resignation, despite challenges within the Accounting Information System environment. The researcher employed path analysis techniques, incorporating job satisfaction as a mediator. The study utilized SmartPLS 3.2.9 for regression analysis. The primary data, collected through an online questionnaire distributed via Google Forms to employees in accounting, finance, and tax at different hierarchical levels, were used. The results suggest that a robust Accounting Information System positively impacts job satisfaction but has no direct effect on resignation intention. Instead, it influences resignation intention through job satisfaction. The study found that the impact of the Accounting Information System on Gen Z respondents did not result in resignation intentions, while non-Gen Z respondents had a negative effect. The researcher recommends that financial literacy be increased among Gen Z individuals to appreciate the significance of the Accounting Information System and attain optimal job satisfaction, thereby avoiding resignation intentions.